REHABILITATION OF WOMEN AFTER UNILATERAL SALPINGECTOMY (LITERATURE REVIEW) REHABILITATION OF WOMEN AFTER UNILATERAL SALPINGECTOMY (LITERATURE REVIEW) - Fayzullayeva, M.A.; Tugizova, D.I. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
This literature review focuses on the rehabilitation process of women after unilateral salpingectomy a surgical removal of one of the fallopian tubes. The study explores the multifaceted consequences of the procedure, including physical recovery, psychological well-being, and implications for future fertility. The review synthesizes data from various sources to highlight the need for an individualized and multidisciplinary rehabilitation approach, including hormonal balance monitoring, emotional support, lifestyle modifications, and fertility counseling. Attention is also given to long-term follow-up, the risk of complications, and the role of minimally invasive techniques in enhancing postoperative outcomes. The review underscores that comprehensive rehabilitation not only improves recovery but also supports the overall health and reproductive potential of women undergoing unilateral salpingectomy.